IMPROVING STUDENTS’ READING COMPREHENSION THROUGH PQRST TECHNIQUE OF ELEVENTH GRADE AT SMA NEGERI 1 KAPONTORI - Baharudin Adu; Baharudin Baharudin; Muh. Zakaria Edi (English Education Department, 2023)
The problem statement of this research was whether there was any difference of reading comprehension of students who have tought using PQRST technique and students who are not thought by this method. The research was quantitative research using quasi-experimental design with a non-equivalent control group. The population was all of students in eleventh grade of SMA Negeri 1 Kapontori that consist 136 students. The sample was taken by using cluster sampling technique consisting of IX Mathematics and Natural science 2, and IX Mathematics and Natural science 3 that contains 28 students in each class. The instrument used was a multiple choice test with 25 questions. Data collected by the result of pre-test and post-test from each class. Then analyzed by using descriptive analysis and inferential analysis. Based on the result of the research, the mean score of the experimental class was 59.14 in pre-test, and 71.14 in post-test. While the mean score in control class was 62.15 in pre-test and 66.78 in post-test. The outcome of the hypothesis testing by using independent sample T-Test, found that the sig. 2 tailed was 0.00 smaller than 0.05. In the other words, H0 is rejected and HI is accepted, so that it can be conclude that there is significant difference between students who have taught by using PQRST technique and students who have taught using conventional method of eleventh grade at SMA Negeri 1 Kapontori.